Optical Buffer Device Employing VO2 Embedded on SOI Waveguides With Microring Resonator - Lina Fan; Yi Li; Wenqing Zhao; Junxian Li; Xin Zhang; Chuang Peng; Yuda Wu; Mengdi Zou; Baoying Fang; Xiaohua Wang (IEEE Photonics Journal)
Phase-change materials (PCMs) have become as promising elements in silicon photonic systems. We propose an optical buffer device based on vanadium dioxide (VO2) embedded on silicon-on-insulator waveguides with a microring resonator. The upload straight waveguide is for coupling light signal from the input port into VO2 embedded on microring resonator and the download straight waveguide with VO2 films is for coupling the storage signal to the output port. The optical characteristics of optical buffer device under different structural parameters are analyzed by using finite difference mode simulation (MODE). By controlling the phase state of VO2 in two coupling regions, the buffer speed of the device can be up to 0.5 ps and buffer time up to 78.28 ps. The optical buffer based on VO2 is a new way for PCM optical buffer.